2019
DOI: 10.1111/hsc.12777
|View full text |Cite
|
Sign up to set email alerts
|

How do residents of aged care homes perceive physical activity and functional independence? A qualitative study

Abstract: Limited evidence exists concerning knowledge and understanding of how to optimally support residents’ physical activity, mobility and functional independence in residential aged care homes. An interpretive qualitative study was conducted to explore residents’ perceptions and experiences of opportunities for physical activity and functional independence, and how physical activity and functional independence are challenged in their care home environment. Purposefully sampled 24 participants (male = 13) from five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…As expected, those with more pain, lower function, more agitation, and more depressive symptoms had lower quality of life. Prior research has shown associations between pain and quality of life ( Brennan et al, 2019 ;Coutinho et al, 2019 ;Jeon et al, 2019 ;Kalinowski et al, 2019 ;Wróblewska et al, 2019 ). One prior study ( van Kooten et al, 2017 ), however, using multiple regression analyses to test the association between pain and neuropsychiatric symptoms and quality of life among nursing home residents with moderate to severe impairment reported that pain was not associated with quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, those with more pain, lower function, more agitation, and more depressive symptoms had lower quality of life. Prior research has shown associations between pain and quality of life ( Brennan et al, 2019 ;Coutinho et al, 2019 ;Jeon et al, 2019 ;Kalinowski et al, 2019 ;Wróblewska et al, 2019 ). One prior study ( van Kooten et al, 2017 ), however, using multiple regression analyses to test the association between pain and neuropsychiatric symptoms and quality of life among nursing home residents with moderate to severe impairment reported that pain was not associated with quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Pain has also been noted to directly influence function ( Brennan et al, 2019 ;Coutinho et al, 2019 ;Jeon et al, 2019 ;Kalinowski et al, 2019 ) and quality of life ( Coutinho et al, 2019 ;Wróblewska et al, 2019 ). Because individuals with severe dementia cannot always communicate pain verbally, pain often presents as aggression, agitation, repetitive vocalizations, withdrawal, apathy, confusion, and impaired or worsening of function ( Kaiho et al, 2017 ).…”
mentioning
confidence: 99%
“…Previous studies have identified that AL residents may believe increased sedentary behavior is an inevitable part of aging (Kotlarczyk et al, 2020; Voss et al, 2020a) and it is important to recognize that this belief is likely related to aging stereotypes of poor physical functioning and dependency (Dionigi, 2015). Interventions should promote positive views of aging by addressing ageist attitudes of inevitable decline and the perception that structured physical activities are inappropriate for older adults (Jeon et al, 2019; Menkin et al, 2022). Promoting positive views of aging may motivate older adults to participate in physical activity and improve their quality of life by helping them engage in meaningful activities (Jeon et al, 2019; Menkin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A população institucionalizada diariamente não é requisitada a desempenhar grande parte das atividades instrumentais e logicamente é natural que o seu desempenho neste tipo de tarefas seja limitado [41]. Para além disso, os instrumentos usados basearam-se em respostas dadas pelos idosos, sendo que a sua perceção de autonomia possa estar influenciada pelo processo de institucionalização, tal como confirmado pelo estudo de Jeon et al [42]. Neste estudo, os autores concluem que a perceção de autonomia pode estar influenciada por alguma diversidade de fatores como a prática de atividade física, a idade avançada, a morte de alguém próximo, a dor e o nível de suporte providenciado pela própria instituição [42].…”
Section: /15unclassified
“…Para além disso, os instrumentos usados basearam-se em respostas dadas pelos idosos, sendo que a sua perceção de autonomia possa estar influenciada pelo processo de institucionalização, tal como confirmado pelo estudo de Jeon et al [42]. Neste estudo, os autores concluem que a perceção de autonomia pode estar influenciada por alguma diversidade de fatores como a prática de atividade física, a idade avançada, a morte de alguém próximo, a dor e o nível de suporte providenciado pela própria instituição [42]. Assim, futuras investigações no contexto específico de idosos institucionalizados, devem incluir a avaliação deste conjunto de fatores.…”
Section: /15unclassified